Clinical comparison between two stabilization methods in distal tibial angular deviation corrected by the CORA method - dos Santos Malta, Caio Afonso; Lopes Muzzi, Leonardo Augusto; Pacheco, Larissa Teixeira; Garcia Perez Neto, Daniel Munhoz; Pires, Vanessa Matos; de Andrade, Caroline Ribeiro; Lázaro Muzzi, Ruthnéia Aparecida (Acta Scientiae Veterinariae, 2020)
Background: Angular deformity is characterized by the deviation of part of the bone that can occur in three different planes, frontal, sagittal and transverse. Trauma on physeal plates is the most common cause of angular deviations of the limbs in dogs. Currently the CORA (Center of Rotation of Angulation) methodology is the best way to evaluate and surgically correct these deformities. The objective of this study is to describe the surgical procedures performed to treat the uniapical valgus deviation affecting both tibial bones in a dog, comparing the outcomes of hybrid external skeletal fixator used in the right pelvic limb in relation to the locking plate used in the left pelvic limb. Case: A 10-month old Border Collie dog was attended at the University Veterinary Hospital with history of lameness and deviation of both pelvic limbs. In the orthopedic examination, it was possible to identify bilateral valgus deviation in the region of the tibio-tarsal joints and moderate lameness, with absence of pain or joint crepitation. Radiographic examination showed that the deformity was only uniapical in the frontal plane, affecting both tibial bones of the dog. Signs of osteoarthrosis were not observed and the preoperative examinations were within the normal limits for the species. The deformities were corrected in two surgical times starting with the procedure in the right tibia, which appeared to be clinically worse. Due to the fact that it was a bilateral affection and there was not a healthy pelvic limb to obtain the normal angles values of this dog, for planning according to the CORA methodology, the values of the tibial mechanical angles for dogs of similar size were taken from the literature. For surgical correction of the right tibia, a closed wedge osteotomy was performed following the second rule of Paley, with bone stabilization using type IB hybrid external skeletal fixator (ESF). The radiographic follow-up was done every 30 days postoperatively, however at 60 days the dog presented with severe lameness and the ESF had to be removed due to the breaking of one of the wires that composed the ring of the hybrid system. The limb continued to be treated by external bandages and total bone healing occurred at 210 days after surgery. Only after the complete recovery of the right limb, the left pelvic limb was operated and was also corrected by closed wedge osteotomy from the second Paley’s rule. However, the bone stabilization was achieved with the use of a T-shaped locking plate. Radiographic follow-up was performed every 30 days postoperatively and at 60 days the osteotomy gap was already consolidated and the dog showed good weight bearing in the pelvic limbs without signs of lameness or pain. Discussion: Currently, it is indicated that bone deformities in small animals should be corrected using the CORA methodology. The hybrid ESF is one of the most commonly used fixation systems for bone stabilization after corrective osteotomies due to great versatility, however, the reported complication rates are relatively high. The locking plates with special shapes, such as the "T" plate used in this study, provide the stable fixation of osteotomies with limited bone stock, as they allow the introduction of larger number of screws per area. Thus, this latter type of implant becomes advantageous for the correction of bone deformities close to the joints. It is concluded that CORA methodology is really effective in the planning of corrective surgeries of angular deviations in dogs. In this case report, the resulting tibial angles after the surgical corrections were within the normal range for healthy dogs of similar size. However, the use of locking plate provided better results with early bone healing and fewer complications than the type IB hybrid ESF.